Underwater Acoustics - Zak, Andrzej (IntechOpen, 2017)
Underwater acoustics, despite the relatively short history, has already found practical application in many areas of human activity. It allows, among others, depth research, data transmission, and underwater observation and provides maritime transport safety and security against terrorists. Moreover, underwater acoustic technologies are also widely used in medicine, biology, and many other fields. Therefore, it is one of the most developing areas. This book is a collection of experiences of scientists from around the world engaged in research, design, and construction, as well as the daily use of underwater acoustic systems. Giving this book in the hands of the reader, we hope that it will be a treasure trove of knowledge and inspiration for further research in the field of underwater acoustics.